2018
DOI: 10.1111/bjso.12260
|View full text |Cite
|
Sign up to set email alerts
|

Future time perspective and interpersonal empathy: Implications for preferring autonomy‐ versus dependency‐oriented helping

Abstract: We examined whether potential help givers' future time perspective (FTP) accounts for the decision to give a person in need dependency-oriented help (i.e., providing the complete solution) or autonomy-oriented help (i.e., providing the means to solve a problem). In addition, building on past research on the effects of empathy in help giving decisions, the present research explored whether helpers' willingness to offer specific type of help is predicted by the interaction between FTP and interpersonal empathy. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 75 publications
0
6
0
Order By: Relevance
“…Although it would intensify the stress responses, empathy would also evoke individuals’ altruistic motivation to provide help, comfort others’ sufferings, and engage in volunteering, enhancing intimate bonds with others (Batson, 2014; Goetz et al, 2010; Jiang et al, 2021; Shiota et al, 2006). Such a prosocial reaction would be beneficial to emotional health (e.g., positive emotion enhancement, posttraumatic growth, and reduction of the risk for psychiatric symptoms) (Hu et al, 2021), and this positive impact would become salient when an individual has a high level of perceived control over the future (Batson, 1987; Chernyak-Hai & Halabi, 2018). Existing literature showed that individuals with high perceived control over the future were likely to exhibit various positive psychological qualities, such as hopefulness and optimism, that were determinants of prosocial behaviors (Minton et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Although it would intensify the stress responses, empathy would also evoke individuals’ altruistic motivation to provide help, comfort others’ sufferings, and engage in volunteering, enhancing intimate bonds with others (Batson, 2014; Goetz et al, 2010; Jiang et al, 2021; Shiota et al, 2006). Such a prosocial reaction would be beneficial to emotional health (e.g., positive emotion enhancement, posttraumatic growth, and reduction of the risk for psychiatric symptoms) (Hu et al, 2021), and this positive impact would become salient when an individual has a high level of perceived control over the future (Batson, 1987; Chernyak-Hai & Halabi, 2018). Existing literature showed that individuals with high perceived control over the future were likely to exhibit various positive psychological qualities, such as hopefulness and optimism, that were determinants of prosocial behaviors (Minton et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…This is not simply a quirk of human thought. A future temporal orientation promotes goal setting and motivation, but can also elicit anxiety (Fried & Slowik, ; Zimbardo & Boyd, ) and interpersonal empathy (Chernyak‐Hai & Halabi, ). In contrast, sentimental longing for the past (i.e., nostalgic reverie) fosters well‐being and counteracts loneliness (for a review, see Sedikides, Wildschut, Arndt, & Routledge, ), but can also elicit distress (i.e., rumination) that harms psychological and physiological health (Nolen‐Hoeksema, ).…”
Section: Introductionmentioning
confidence: 99%
“…In the current research, we expected that time perceptions related to the collective future would moderate the associations between emotions and support for conciliatory versus aggressive policies. Specifically, given the notion that future perspective “orients people toward potential future outcomes of interpersonal relationships” (Chernyak‐Hai & Halabi, 2018, p. 795) and an intractable conflict, collective future orientation may elevate or exacerbate the attitudinal implications of emotions. Particularly, because intractable conflicts make the future uncertain and are extremely threatening to both the group and the individual (Bar‐Tal, Chernyak‐Hai, et al, 2009), and because they orient people toward historical narratives that make the past live on (Bar‐Tal et al, 2014), time orientation may play an important role in attitudinal outcomes associated with them.…”
Section: Collective Time Perspective and Future Orientationmentioning
confidence: 99%
“…Empathy is an emotional phenomenon shown to promote intergroup attitudes and motivate intergroup help (e.g., Dovidio et al, 2010;Rosler et al, 2017;Stürmer et al, 2006). Previous work has demonstrated that empathic concern promotes willingness to reduce outgroup hardship (see Chernyak-Hai & Halabi, 2018;Rosler et al, 2017). However, while the role of hatred and hope has been extensively investigated, the role of empathy in promoting prosocial behavior toward the outgroup is less clear (e.g., Cikara et al, 2011).…”
Section: Introductionmentioning
confidence: 99%